2013
DOI: 10.1097/pdm.0b013e31827fedcc
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 2 Real-Time PCR Assays for In Vitro Diagnostic Use in the Rapid and Multiplex Detection of EGFR Gene Mutations in NSCLC

Abstract: Activating mutations of the epidermal growth factor receptor (EGFR) gene in non-small cell lung cancer predict for a favorable clinical response to tyrosine kinase inhibitor therapy. Although Sanger sequencing is a conventional method to detect EGFR gene mutations, multiplex real-time allele-specific polymerase chain reaction (PCR) systems are increasingly used in the routine molecular diagnostic setting. We aim to evaluate 2 proprietary real-time PCR assays (cobas and therascreen) against Sanger sequencing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Allele-specific real-time PCR has been widely used in detecting EGFR “hotspot” mutations in cancerous tissues [[10], [11], [12], [13], [14], [15]]. Therascreen ® (Qiagen) is a FDA-approved real time PCR in vitro diagnostic (IVD) test that may be used to detect 21 EGFR mutations in exons 18, 19, 20, and 21 against a background of wild type genomic DNA [16].…”
Section: Introductionmentioning
confidence: 99%
“…Allele-specific real-time PCR has been widely used in detecting EGFR “hotspot” mutations in cancerous tissues [[10], [11], [12], [13], [14], [15]]. Therascreen ® (Qiagen) is a FDA-approved real time PCR in vitro diagnostic (IVD) test that may be used to detect 21 EGFR mutations in exons 18, 19, 20, and 21 against a background of wild type genomic DNA [16].…”
Section: Introductionmentioning
confidence: 99%
“…A further study comparing 4 targeted methods with Sanger sequencing found that although the targeted methods had similar LODs their efficacy when testing lung cancer samples varies; in this cohort PNA‐LNA Clamp PCR was found to have the highest rates of analytical failure and discordance . Two studies which directly compared Therascreen with COBAS showed both assays to have similar assay performance …”
Section: Methodsmentioning
confidence: 91%
“…Compared to Sanger sequencing, 100% sensitivity and specificity have been reported for the Therascreen assay28 , and the Cobas EGFR assay showed equal or superior performance29,30 . However, in another study, these assays performed suboptimally, under calling mutations as compared to Sanger sequencing (89% and 88% concordance rates with Sanger for Cobas and Therascreen assays, respectively)31 . Other technologies are designed to query mutations in several different cancer-associated genes, including EGFR.…”
mentioning
confidence: 95%